NF-κB activation during intradermal DNA vaccination is essential for eliciting tumor protective antigen-specific CTL responses - Ligtenberg, Maarten A (Landes Bioscience, 2013)
DNA vaccines have been shown to elicit tumor-protective cytotoxic T lymphocyte (CTL) immunity in preclinical models, but have shown limited efficacy in cancer patients. Plasmids used for DNA vaccines can stimulate several innate immune receptors, triggering the activation of master transcription factors, including interferon regulatory factor 3 (IRF3) and nuclear factor κ B (NF-κB). These transcription factors drive the production of type I interferons (IFNs) and pro-inflammatory cytokines, which promote the induction of CTL responses. Understanding the innate immune signaling pathways triggered by DNA vaccines that control the generation of CTL responses will increase our ability to design more effective vaccines. To gain insight into the contribution of these pathways, we vaccinated mice lacking different signaling components with plasmids encoding tyrosinase-related protein 2 (TRP2) or ovalbumin (OVA) using intradermal electroporation. Antigen-specific CTL responses were detected by intracellular IFN-γ staining and in vivo cytotoxicity. Mice lacking IRF3, IFN-α receptor, IL-1β/IL-18, TLR9 or MyD88 showed similar CTL responses to wild-type mice, arguing that none of these molecules were required for the immunogenicity of DNA vaccines. To elucidate the role of NF-κB activation we co-vaccinated mice with pIκBα-SR, a plasmid encoding a mutant IκBα that blocks NF-κB activity. Mice vaccinated with pIκBα-SR and the TRP2-encoding plasmid (pTRP2) drastically reduced the frequencies of TRP2-specific CTLs and were unable to suppress lung melanoma metastasis in vivo, as compared with mice vaccinated only with pTRP2. Taken together these results indicate that the activation of NF-κB is essential for the immunogenicity of intradermal DNA vaccines.